Tuberculosis Arthritis in the Wrist While Using Rituximab for Rheumatoid Arthritis Treatment - Ulusoy H (Dove Medical Press, 2020)
Hasan Ulusoy,1 Özge Acar Cakan,1 Tibel Tuna2 1Division of Rheumatology, Department of Physical Medicine and Rehabilitation, Faculty of Medicine, Ondokuz Mayis University, Samsun, Turkey; 2Department of Pulmonary Medicine and Tuberculosis, Faculty of Medicine, Ondokuz Mayis University, Samsun, TurkeyCorrespondence: Hasan UlusoyOndokuz Mayis Universitesi, Tip Fakultesi, Romatoloji Bilimdali, Fiziksel Tip ve Rehabilitasyon AD, Samsun 55200, TurkeyTel +90 534 074 05 55Email drhasanulusoy@gmail.comIntroduction: Data from clinical trials indicate that there are no increased risk of tuberculosis (TB) infections in rheumatoid arthritis (RA) patients while using rituximab (RTX). Herein, we report a RA patient who developed TB arthritis while using RTX.Case Report: A 49-year-old patient was treated with methotrexate and prednisolone along with RTX for two years. Later, she presented with increasing pain, swelling, redness and cutaneous fistulization in her left wrist for two months. The lesion on the wrist was debritted. Histopathologic evaluation revealed the presence of acid-fast bacilli. Polymerase chain reaction test and culture confirmed mycobacterium tuberculosis. RTX, methotrexate and prednisolone were withdrawn. The patient was treated with 12-month course of antituberculous treatment and responded well. The patient, who did not have pain or swelling in her other joints, was not given any treatment for RA after antituberculous treatment.Conclusion: Clinicians should keep in mind that TB infections may be encountered while using RTX. Latent TB screening may be appropriate in patients using concomitant corticosteroid and living in TB endemic areas.Keywords: rheumatoid arthritis, rituximab, tuberculosis, infection